Oracy skills evaluation of students' RP performance through lecturer's, self and peer assessment / Shun Chone Liaw ... [et al.] - Shun, Chone Liaw; A/L Marimuthu, Rasaya; Teck, Heng Lim; Boon, Yih Mah; Foo Terng, Hoe (UiTM Cawangan Johor, 2018)
Role-play (RP) is an educational method mainly utilized to develop team presentational skills, interdependence and peer feedback. In addition, RP provides great opportunities to train and demonstrate oracy skills among group members. At universities, students passively rely on lecturers to assess their oracy skills in RP activities. In this study, students' RP performance were evaluated by the lecturer, self and peers. The objectives of this research are: firstly, to determine the levels of agreement of assessing students' RP performance among lecturer, self and peers. 104 diploma hotel students were divided into small groups and needed to RP and their performance recorded in video clips. Findings showed there were almost similar significant differences in oracy skills evaluation scores between lecturers and self as well as between lecturer and peer while there was no significant difference in evaluation scores between self and peer evaluation in four dimensions of oracy skills such as physical, linguistics, cognitive and social and emotional domains. However, oracy skills were perceived by the students to have improved slightly in confidence level and teamwork. In conclusion, there were significant differences between oracy skills evaluation scores between lecturers and students (be it self or peer assessed) but students perceived a heightened level of their performance in oracy skills due to constructive feedbacks during their RP video- taped activity.